Teaching English Using Local Culture Content Short Story - Sanda, Silfi (English Education Department, Universitas Islam Indonesia, 2009)
This paper is mainly about the use of local culture content short story in developing students' English proficiency and some activities that can be employed for this purpose. The local culture exposed in the short story is the traditional woven clothes of Palembang, Songket in term of process and product. The short story used in this topic is Cek Ipah